Formas De Integração E ‘Tríade Mercantil’: O Carácter Não Ontológico Do Mercado Na Análise Institucional De Karl Polanyi (Forms of Integration and ‘Catallactic Triad’: The Non-ontological Character of Market in the Institutional Analysis of Karl Polanyi) - Machado, Nuno Miguel Cardoso (Social Science Research Network, 2013)
A análise da economia enquanto processo instituído, proposta por Polanyi, concretiza-se no estudo dos padrões institucionais que esta pode assumir empiricamente: reciprocidade, redistribuição e troca mercantil. Esta última – corporizada num sistema de mercados autorregulados – apenas se assume como forma de integração dominante nas sociedades capitalistas modernas. O estudo das formas de integração – assim como a sua extensão lógica à análise dos conceitos de comércio, dinheiro e mercado – permitirá que as ciências sociais evitem uma visão marcada pela ‘mentalidade de mercado’, ou ‘falácia economicista’. Se o comércio e o dinheiro têm acompanhado a humanidade desde os seus primórdios, os mercados são um desenvolvimento institucional bem mais recente.The analysis of the economy as instituted process, suggested by Polanyi, consists in the study of the institutional patterns which the economy may assume empirically: reciprocity, redistribution and market exchange. The last one – embodied in a system of price-making markets – only comes to be a dominant form of integration in modern capitalist societies. The study of the forms of integration – as well as its logical extension to the analysis of the concepts of trade, money and market – will allow social sciences to avoid a framework characterized by a ‘market mentality’, or ‘economistic fallacy’. Trade and money have existed since the early stages of mankind but markets are a more recent institutional development. in Teoria & Sociedade, Forthcoming
Keywords: exchange; market; reciprocity; redistribution

Karl Polanyi E O ‘Grande Debate’ Entre Substantivistas E Formalistas Na Antropologia Econômica (Karl Polanyi and the 'Great Debate' Between the Substantivists and Formalists in Economic Anthropology) - Machado, Nuno Miguel Cardoso (Social Science Research Network, 2012)
Na raiz do pensamento Polanyiano, encontra-se a distinção entre economia no sentido substantivo e economia no sentido formal. Com efeito, a concepção substantivista que define a economia como um processo instituído de interação entre o homem e o ambiente natural e social que o rodeia e resulta em contínua oferta de meios para satisfazer as necessidades humanas constitui a base do método preconizado pelo autor: a análise institucional. Com tal distinção, Polanyi (1977a) pretende evitar a "falácia economicista" que consiste na identificação automática da economia com sua forma de mercado. Ao contrário, só na moderna economia capitalista é que um "sistema de mercados formadores de preços" desempenha papel fundamental. Essas questões foram alvo de um "Grande Debate" entre as correntes substantivista – encabeçada por Polanyi – e formalista no contexto da disciplina da Antropologia Econômica.At the root of Polanyian thought, a distintiction can be found between the substantive and formal concepts of the economy. In fact, the substantivist conception, that defines the economy as an instituted process of interaction between man and its natural and social environment, which results in a continuous supply of material means to meet human needs, constitutes the basis of the method recomended by the author: institutional analysis. With this distinction, Polanyi intends to avoid the "economistic fallacy", which consists of the automatic identification of the economy in its market form. Only in the modern capitalist economy does a system of "price-making markets" play a fundamental role. These questions were amply discussed in the so-called "Great Debate" between the substantivist and formalist schools of thought in the discipline of Economic Anthropology. in Economia e Sociedade, Vol. 21, No. 1 (44), pp. 165-195
Keywords: economy; formalism; institutional analysis; market; substantivism

Karl Polanyi and the New Economic Sociology: Notes on the Concept of (Dis)Embeddedness - Machado, Nuno Miguel Cardoso (Social Science Research Network, 2011)
Within the context of the New Economic Sociology, Karl Polanyi is almost universally considered the "father" of the concept of embeddedness. However, this concept has been subject to selective appropriation by this discipline and its relationship to the remaining theoretical edifice constructed by Polanyi has been neglected. It is, in fact, possible to refer to the "great transformation" to which the concept of embeddedness has been subjected: whereas in Polanyi’s work it is associated with the macro(economic) level and is used as evidence of the exceptional nature of the capitalist market economy –- disembedded from society –- in NES, it is normally associated with the meso (and even micro) level, on the assumption that all economies –- including capitalist economies -– are embedded. in RCCS Annual Review, No. 3, pp. 119-140
Keywords: Karl Polanyi; capitalism; embeddedness; market economy; new economic sociology

Avez-vous lu Polanyi ? - Maucourant, Jérôme (HAL, 2011)
"Cette étude présente le parcours intellectuel de Karl Polanyi (1886-1964), à la croisée de l'économie, de l'histoire et de la sociologie, et propose une synthèse de l'ensemble de son oeuvre." Postface accessible en ligne : [ http://www.contretemps.eu/lectures/bonnes-feuilles-avez-vous-lu-polanyi-j%C3%A9r%C3%B4me-maucourant-postface ]
Keywords: Great Transformation, The (Book); La Grande Transformation; critique and interpretation; critique et interprétation; libéralisme; économie politique

The Idea of a Three-Dimensional Conflicts Law as Constitutional Form - Joerges, Christian (RECON Online Working Paper 2010/05, 2010)
‘Constitutionalisation’ is the key concept in the search for legitimate governance in the European Union and in the international system. This paper suggests the revitalising of a discipline which is widely neglected in European law and international law scholarship. It does not, however, recommend a return to the conflict of laws (private international law) in the traditional sense. The new type of conflicts law that the paper advocates is not concerned with selecting the proper legal system in cases with connections to various jurisdictions. This conflicts law is conceptualised as a response to the increasing inter-dependence of formerly more autonomous legal orders and to the democracy failure of constitutional states which result from the external effects of their laws and legal decisions on foreign systems and on their citizens who cannot understand themselves as their authors. European law has a vocation and many means both to compensate for the democracy failures of member states and to build upon this potential in its constitutionalisation. The conflicts law approach also provides new, albeit more restrained, perspectives at international level. WTO law is used to explore and document its constitutional perspectives. The conflicts law approach is differentiated into three dimensions. With this differentiated fabric, the approach responds to transformation processes which have affected contemporary law at all levels of governance after the rise of regulatory politics and the turn to governance. In its second dimension, conflicts law seeks to constitutionalise co-operative problem-solving under the lead of administrative bodies, while its third dimensions is concerned with both the recognition and the supervision of transnational governance arrangements and para-legal regimes.
Keywords: BLOCK, Fred; Europeanisation; World Trade Organization (WTO); always socially embedded' economy; constitutionalisation; deliberative democracy; economic law; economic sociology; multilevel governance; private international law; rule of law; social embeddedness; social regulation; supranationalism

The Great Transformation of Embeddedness: Karl Polanyi and the New Economic Sociology - Beckert, Jens (Social Science Research Network, 2007)
I argue that in its adaptation from Karl Polanyi’s The Great Transformation, the concept of embeddedness has itself undergone a great transformation. In the process, significant meanings of the concept have vanished, while others have been added. First I explore the different meanings the concept of embeddedness has achieved in the new economic sociology. Then I argue that it is not the embeddedness of economic action that should constitute the vantage point of economic sociology, but rather three coordination problems that actors face in economic exchange: the valuation of goods, competition and the problem of cooperation deriving from the social risks of exchange. I show that by proceeding from these coordination problems economic sociology, economic anthropology and economic history can find common research questions which allow them to enter into dialogue with each other more systematically. In the next section I focus on the social-reformist inclinations of Polanyi’s use of the notion of embeddedness and thereby highlight a challenge posed in The Great Transformation that was largely not taken up by economic sociologists. Finally, I discuss limitations for developing a macro theory of the economy that result from making embeddedness the core concept of economic sociology.
Keywords: economic history; economic sociology; embeddedness; political economy